Community assembly processes underlying the temporal dynamics of glacial stream and lake bacterial communities. - Gu, Z.; Liu, K.; Pedersen, M. W.; Wang, F.; Chen, Y.; Zeng, C.; Liu, Y.
Community assembly processes are important in structuring aquatic microbial communities; however, the influence of these processes on the dynamics of bacterial communities in glacial streams and lakes remains largely unstudied. To investigate the assembly processes underlying the temporal variation of the bacterial community, we collected 50 water samples over five months in an ephemeral glacial stream and its downstream lake at the terminus of the Qiangyong glacier on the Tibetan Plateau. Using the V4 hypervariable region of the bacterial 16S rRNA gene combined with environmental measurements, such as water temperature, pH, total nitrogen (TN), dissolved organic carbon (DOC)and water conductivity, we found that temporal variation in the environmental factors promoted the shift in the proglacial stream and the lake bacterial communities. The quantification of ecological processes showed that the stream microbial communities were influenced by the ecological drift (40percent)in June, then changed to homogeneous selection (40percent)in July and variable selection (60percent)in September, while the dynamic pattern of proglacial lake bacterioplankton was governed by homogeneous selection (? 50percent)over the time. Overall, the dynamic of bacterial community in the proglacial stream and lake water is influenced by environmental factors, and the community composition assembly of the Qiangyong glacial stream and lake could be dynamic and primarily governed by deterministic processes.
Keywords: MICROBIAL ECOLOGY; GLACIERS; TEMPORAL VARIATION; COMMUNITY ASSEMBLY